Manufacturing of geared sheet metal components using flexible rolled tailored blanks - Opel, Simon; Schneider, Thomas; Merklein, Marion (Key Engineering Materials, 2013)
Manufacturing of functional sheet metal products with integrated gear teeth by forming can be realized with the application of bulk forming operations on sheet metals. The main challenges of sheet-bulk metal forming are high resulting forming forces and the demand on a specific control of the material flow. In addition, there is a distinctive interaction between blank thickness and resulting part quality. To meet these challenges at high material efficiency, the application of tailored blanks with a defined sheet thickness distribution is a promising way. The process adapted semi-finished products used in the presented work are formed by a flexible rolling process. Firstly the developed rolling machine to produce rotational symmetric tailored blanks is shown, as well as the fundamental process influences during rolling. Based on that, the development of a suitable process strategy to produce tailored blanks with a thickened sheet area is presented. The further processing of those tailored blanks for the realization of external geared sheet metal components will show the advantages compared to the application of conventional sheet metals of constant sheet thickness. Therefore the concept of a combined deep drawing process with geared drawing die and optional upsetting is presented. The results show, that on the one hand the material efficiency is increased in comparison to the usage of conventional sheets of the same maximum thickness. On the other hand, the application of flexible rolled tailored blanks improves mold filling of the gear teeth and the component's strength. These approaches prove that the application of rolled tailored blanks is an appropriate procedure to enhance the limits of using conventional sheet metals within sheet-bulk metal forming. Copyright © 2013 Trans Tech Publications Ltd.
LFT Import::2019-07-29 (1858)
Keywords: Flexible rolling; Ironing; Sheet-bulk metal forming